P013 Screening practices related to inconclusive neisseria gonorrhoeae and chlamydia trachomatis nucleic acid amplification testing. (14th July 2019) - Blair, Cherie; Garner, Omai; Pedone, Bettina; Elias, Sam; Landovitz, Raphael
Abstract : Background: Given rising incidence of Neisseria gonorrhoeae and Chlamydia trachomatis (GC/CT), development of efficacious screening strategies is critical. While guidelines recommend nucleic acid amplification testing (NAAT) for GC/CT screening, a small proportion of NAAT results are inconclusive - resulting in delays in diagnosis and treatment. Our study seeks to determine rates as well as provider- and patient-related factors associated with inconclusive NAAT results with the goal of developing improved screening practices. Methods: This is a cross-sectional, case-control study of individuals with inconclusive GC/CT NAATs at a single institution (University of California, Los Angeles) from 3/2016–6/2018. Clinical charts were abstracted for age, gender, HIV status, PrEP use, STI screening (GC/CT and syphilis), anatomic site of sample collection (urogenital, pharyngeal, or rectal), and whether repeat testing occurred within 6 months following an inconclusive result. Cases were defined as a specimen that resulted in inconclusive GC and/or CT NAAT. Controls were specimens randomly selected from all non-inconclusive samples that underwent GC/CT NAAT during the study period and were matched with inconclusive specimens by type (rectal, urine, or genital). Patient-level characteristics associated with inconclusive GC/CT testing were analyzed with Chi-square and logistic regression. Results: During the study period, 6.1% (852/14, 048) rectal, 0.3% (313/91, 092) genital, and 0.01% (155/137, 783) urine samples were inconclusive for one or both of GC and CT; no pharyngeal samples yielded inconclusive results. Among patients with inconclusive GC/CT NAAT, 64.6% (441/683) received repeat testing within six months, of which 6.4% were positive, 82.8% (365/441) negative, 10.7% (47/441) inconclusive, and 0.2% (1/441) indeterminate. While diabetes was associated with inconclusive urogenital GC/CT NAAT, HIV status, PrEP use, and positive STI screening were not associated with inconclusive results. Conclusion: Despite having a clinical indication to receive GC/CT screening, fewer than two-thirds of inconclusive results were repeated, potentially missing an opportunity to interrupt the infection cycle. Disclosure: No significant relationships.